2015
DOI: 10.1371/journal.pone.0144180
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Agenesis of the Mandibular Second Premolar from Adjacent Teeth

Abstract: Early diagnosis of agenesis of the mandibular second premolar (P2) enhances management of the dental arch in the growing child. The aim of this study was to explore the relationship in the development of the mandibular first molar (M1) and first premolar (P1) at early stages of P2 (second premolar). Specifically, we ask if the likelihood of P2 agenesis can be predicted from adjacent developing teeth. We selected archived dental panoramic radiographs with P2 at crown formation stages (N = 212) and calculated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…It is explained by the fact that bone formation rate is high during the mandibular alveolar process. [ 32 ] In agreement with our study, Kavitha et al [ 33 ] suggested that MCW is significantly associated with age and could be considered as a valuable parameter for evaluating the bone strength and osteoporosis regarding postmenopausal women in their study on Korean population. Moreover, Roberts et al[ 34 ] reported that MCW starts to decrease in women and men at ages 42.5 and 36 years, respectively.…”
Section: Discussionsupporting
confidence: 92%
“…It is explained by the fact that bone formation rate is high during the mandibular alveolar process. [ 32 ] In agreement with our study, Kavitha et al [ 33 ] suggested that MCW is significantly associated with age and could be considered as a valuable parameter for evaluating the bone strength and osteoporosis regarding postmenopausal women in their study on Korean population. Moreover, Roberts et al[ 34 ] reported that MCW starts to decrease in women and men at ages 42.5 and 36 years, respectively.…”
Section: Discussionsupporting
confidence: 92%
“…Unfortunately, very late development of the mandibular second premolar has been reported in a few cases. To avoid a false-positive diagnosis of agenesis of this tooth, the method proposed by Sharma et al was used [ 26 ]. They suggest that the second premolar in the mandible is highly unlikely to develop if the adjacent first premolar is beyond stage ‘crown complete’ and the first molar is beyond stage ‘root one half’.…”
Section: Discussionmentioning
confidence: 99%
“…Dental anomalies and lesions of the gnathic bones in children can alter tooth eruption, lead to abnormal occlusion and, in some cases, the child's aesthetics and social life may be affected in the future. If early detected, these changes can be surgically or orthodontically treated, especially with interceptive orthodontics, thus reducing functional, psychosocial and financial problems [10]. In addition, panoramic radiography can be used as an initial complementary exam to check whether the chronology of tooth eruption is in line with the expected for the child's age [11].…”
Section: Introductionmentioning
confidence: 99%